Ethical Publishing: How Do We Get There? - Ben Phillips; Denis Bourget; Fernando Racimo; Nicolas Galtier; Noémie Aubert Bonn; Thomas Guillemaud; Véronique De Herde (Philosophy, Theory, and Practice in Biology, 2022)
The academic journal publishing model is deeply unethical: today, a few major, for-profit conglomerates control more than 50% of all articles in the natural sciences and social sciences, driving subscription and open-access publishing fees above levels that can be sustainably maintained by publicly funded universities, libraries, and research institutions worldwide. About a third of the costs paid for publishing papers is profit for these dominant publishers' shareholders, and about half of them covers costs to keep the system running, including lobbying, marketing fees, and paywalls. The paywalls in turn restrict access of scientific outputs, preventing them from being freely shared with the public and other researchers. Thus, money that the public is told goes into science is actually being funneled away from it, or used to limit access to it. Alternatives to this model exist and have increased in popularity in recent years, including diamond open-access journals and community-driven recommendation models. These are free of charge for authors and minimize costs for institutions and agencies, while making peer-reviewed scientific results publicly accessible. However, for-profit publishing agents have made change difficult, by co-opting open-access schemes and creating journal-driven incentives that prevent an effective collective transition away from profiteering. Here, we give a brief overview of the current state of the academic publishing system, including its most important systemic problems. We then describe alternative systems. We explain the reasons why the move toward them can be perceived as costly to individual researchers, and we demystify common roadblocks to change. Finally, in view of the above, we provide a set of guidelines and recommendations that academics at all levels can implement, in order to enable a more rapid and effective transition toward ethical publishing.